Cyberterrorism: Understandings, Debates, and Representations - Stuart Macdonald (The Oxford Handbook of the History of Terrorism, 2021)
This chapter focuses on understandings and debates around cyberterrorism as well as the effect particular representations of this phenomenon have upon assessing its threat. The chapter begins by introducing various understandings of cyberterrorism and differentiates between narrow and broad conceptions as well as effects and intent based definitions. Moving onto consider the threat of cyberterrorism the chapter identifies an ongoing debate between ‘concerned’ and ‘sceptical’ voices as well as those that contest whether cyberterrorism has ever taken place. The chapter then introduces a range of broadly constructivist studies which question the orthodox approach to cyberterrorism as an ontological reality and highlight the importance of media representations of this threat. To illustrate this, the chapter concludes by highlighting findings from a recent study of global news media coverage. It shows that this media is frequently apprehensive in tone, despite the existence of diverse understandings of cyberterrorism and cybersecurity.